Rocaglamide derivatives are immunosuppressive phytochemicals that target NF-AT activity in T cells - Proksch, Peter; Spring, Herbert; Krammer, Peter H.; Li-Weber, Min (The journal of immunology, 2005)
Aglaia (family Meliaceae) plants are used in traditional medicine (e.g., in Vietnam) for the treatment of inflammatory skin diseases and allergic inflammatory disorders such as asthma. Inflammatory diseases arise from inappropriate activation of the immune system, leading to abnormal expression of genes encoding inflammatory cytokines and tissue-destructive enzymes. The active compounds isolated from these plants are derivatives of rocaglamide. In this study we show that rocaglamides are potent immunosuppressive phytochemicals that suppress IFN-γ, TNF-α, IL-2, and IL-4 production in peripheral blood T cells at nanomolar concentrations. We demonstrate that rocaglamides inhibit cytokine gene expression at the transcriptional level. At the doses that inhibit cytokine production, they selectively block NF-AT activity without impairing NF-κB and AP-1. We also show that inhibition of NF-AT activation by rocaglamide is mediated by strong activation of JNK and p38 kinases. Our study suggests that rocaglamide derivatives may serve as a new source of NF-AT-specific inhibitors for the treatment of certain inflammatory diseases.